Characterization of potential probiotic bacteria Enterococcus faecium MC-5 isolated from the gut content of Cyprinus carpio specularis. (November 2022) - Tilwani, Younus Mohd; Lakra, Avinash Kant; Domdi, Latha; Jha, Natwar; Arul, Venkatesan
Abstract: The goal of this study was to determine the unique characteristics of Enterococcus faecium MC-5, a probiotic bacteria isolated from the intestine of a fish, Cyprinus carpio specularis, collected from Dal Lake in Srinagar, Kashmir, India. For this, the important valuable probiotic attributes, some functional properties, and safety assessments were analyzed in-vitro for the strain MC-5. The strain E. faecium MC-5 exhibited high resistance to low pH, high bile salt, lysozyme, and phenol. The strain MC-5 showed excellent auto- and co-aggregation properties and displayed remarkable hydrophobicity towards various tested hydrocarbons which suggested that the strain possesses venerable adhesion properties. Apart from these, the cell-free supernatant (CFS) of strain MC-5 exhibited phenomenal antimicrobial activity against the tested pathogens. A scanning electron microscope (SEM) image revealed strain MC-5 finely adhered to human colon adenocarcinoma cells (HCT-15 cells). The strain MC-5 showed high bile salt hydrolase activity and excellent cholesterol removal ability of 70.27%. The intact cells of strain MC-5 also showed strong DPPH scavenging activity. The EPS produced by E . faecium MC-5 inhibited the adhesion of Listeria monocytogenes, Staphylococcus aureus, and Salmonella enterica on HCT-15 cells with maximum inhibition rates of 41.82, 40.34, and 55.51%, respectively for displacement assay, which was higher as compared to exclusion (26.06, 26.11, and 39.23%) and competition assays (30.06, 26.7, and 41.20%). Strain MC-5 did not exhibit hemolysis and was also found susceptible to vancomycin and other clinically important antibiotics. When evaluating all the results from the present study, it is propounded that strain MC-5 has enviable probiotic characteristics and thus can be used as bio-protective cultures and/or bio-shield in food and pharmaceutical industries. Highlights: Enterococcus faecium MC-5 was isolated from the intestine of a fish, Cyprinus carpio specularis . The strain E. faecium MC-5 exhibited high resistance to low pH, high bile salt, lysozyme, and phenol. SEM image revealed that strain MC-5 finely adhered to human colon adenocarcinoma cells (HCT-15 cells). The strain MC-5 showed high bile salt hydrolase activity and excellent cholesterol removal ability of 70.27%. Strain MC-5 did not exhibit hemolysis and was also found susceptible to vancomycin and other relevant antibiotics.